Análisis del discurso de las noticias sobre el femicidio en el 2020 caso diario El Universo - Rebolledo Montero, Jakeline (2021)
This project is based on an analysis of the discourse issued by the newspaper El Universo when it refers to dead women in charge of their partners or any individual on the street who takes advantage of them as an abuser and aggressor of them. The methods and techniques used for this study were the qualitative and quantitative methods, the interview techniques and the corresponding analysis file instrument of the 2020 digital newspaper Universo, which includes femicide news. The problem of femicide is addressed through the discourse that this medium exposes, starting from the following thematic categories that have helped in the development and analysis of this case study such as: violence, discourse and communication, with the purpose of understanding Under what parameters is a mediated discourse constructed which becomes something natural for the audiences. It presents an analysis through a file with the data of the women killed by femicide and in what way the event occurred, it also finds brief concepts of what femicide is and how the media have been involved in them, such as the cases for homicides and murders.